Types Of Examination Procedures In State Administrative Court - Dea Ananda Amira; Muhammad Ryan Abdillah; Vina Amanda (ISNU Sumatera Utara, 2024)
This study examines the mechanisms of the Administrative Court (PTUN) in resolving disputes between citizens and the government through various types of examination procedures. Three main types of examination procedures discussed are ordinary examination procedures, expedited examination procedures, and shortened examination procedures. The ordinary examination procedure includes key stages such as filing a lawsuit, administrative review, deliberation meetings, and preparatory examination (dismissal process), systematically regulating the legal process for efficiency. Meanwhile, expedited examination procedures are implemented for cases requiring immediate attention, while shortened examination procedures are designed to resolve simpler cases. This study also highlights the importance of guidelines from the Supreme Court, which serve as a reference in the examination process, especially when the plaintiff files an objection to existing rulings. Each type of examination procedure plays a significant role in ensuring justice and legal certainty for the parties involved. With a good understanding of these various examination procedures, it is hoped that legal practitioners and the public can navigate the administrative court process more effectively and efficiently.